2022
DOI: 10.1002/acs.3475
|View full text |Cite
|
Sign up to set email alerts
|

Fully distributed containment of multiple‐input‐multiple‐output linear multi‐agent systems with multiple nonautonomous leaders

Abstract: Summary In this article, we study the fully distributed containment problem for multiple‐input‐multiple‐output linear multi‐agent systems (MASs) with multiple nonautonomous leaders (i.e., leaders with nonzero inputs). First, based on an unknown input observer (UIO) with full order and by using unit vector method, we design an adaptive discontinuous controller, where the adaptive law is used to adjust network coupling strengths. And by using Barbǎlat lemma, we show that fully distributed containment can be ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…where i ∈ F, k ∈ E, u k (t) = −f ( ξk (t), t) and Θ = PBB T P. According to protocols (10) and ( 11), ( 5) and ( 6) can be represented as:…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…where i ∈ F, k ∈ E, u k (t) = −f ( ξk (t), t) and Θ = PBB T P. According to protocols (10) and ( 11), ( 5) and ( 6) can be represented as:…”
Section: Problem Formulationmentioning
confidence: 99%
“…1 For example, networking field, 2 computer field, 3 control science field. 4 There are many valuable studies in the field of control science, including consensus control, [5][6][7][8] containment control, 9,10 tracking control 11 and so on. With the depth of researches, it is found that formation problems have inextricable link to practical applications, such as cluster control of satellites, 12 formation control of unmanned aerial vehicle swarms, 13 and cooperative control of unmanned surface vessel.…”
Section: Introductionmentioning
confidence: 99%
“…With the advances in multi-spacecraft and multi-robotic, the control strategies for multi-agent systems (MASs) have attracted wide publicity, [1][2][3][4] the research in this direction is also continuing to develop and broaden. [5][6][7] There are two types of MASs control strategies, one is consensus control for the MASs with one leader, another is containment control for MASs with multiple leaders which gets more attention in recent years. [8][9][10][11] Because of the complexity of MASs, stochastic disturbances generated by the external environment have great influence on the control effect.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent chattering, some continuous synchronization controllers were designed by using the boundary layer technique. [26][27][28][29][30][31][32][33][34] The continuous controllers, however, can only achieve bounded error synchronization because the effects of targets' nonzero inputs cannot be completely eliminated. 35 While the deterministic communication topology (i.e., fixed or deterministic switching) studied in References 26-34 will limit the applications of proposed controllers since most practical networks switch stochastically due to random links lost or recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is much more favorable to use relative outputs in real applications. By using unit vector method, some discontinuous synchronization controllers based on relative outputs were given in References 30–34. Although the discontinuous controllers can achieve zero error synchronization, they will cause chattering because of the high frequency switchings of discontinuous terms.…”
Section: Introductionmentioning
confidence: 99%